Response of Salvia officinalis to zinc and silicon nanoparticles and pollen extract as alternates to traditional fertilizers - El-Mahrouk, El-Sayed Mohamed; Atef, Ekramy Abdel-Moatamed; Gabr, Mohamed Kadry; Aly, Mahmoud Ahmed; Mohamed, Abdallah E.; Eisa, Eman Abdelhakim; Gururani, Mayank Anand (Frontiers in Plant Science, 2024)
Salvia officinalis is used in a variety of medicinal and aromatic products. The effects of various treatments on sage (Salvia officinalis) plants were investigated in an open-field experiment conducted between 2021 and 2022. During the experiment, ZnO nanoparticles (NPs) were used at concentrations of 1.0 and 1.5 g/L, SiO2 NPs were used at concentrations of 0.1 and 0.2 g/L, and date palm pollen extracts (DPE) were used at concentrations of 15 and 25 g/L, in combination with NPK fertilizers at 75%, 50%, and 25%, respectively, with a control group of 100% NPK fertilizer. A treatment consisting of 75% NPK, 15 g/L DPE, 1.0 g/L ZnO NPs, and 0.1 g/L SiO2 NPs significantly improved vegetative traits and essential oil yield. Compared to the control in the growing seasons of 2021 and 2022, this treatment resulted in increases in plant height, chlorophyll index, fresh and dry weights, and essential oil yield (EOY) per plant of 23.40% and 28.30%, 27.56% and 26.54%, 42.17% and 42.95%, 64.10% and 62.79%, and 93.38% and 91.08%, respectively. Combinations of 25% NPK + 25 g/L DPE + 1.5 g/L ZnO nanoparticles + 0.2 g/L SiO2 NPs and 75% NPK + 0.1 g/L SiO2 NPs produced the highest essential oil percentage (EO%). During the experimental seasons, these treatments increased EO% by 15.45% and 26.25%. In total, 58 substances were identified across the different treatments in the essential oil composition analysis. There were 11 compounds in the 25% NPK, 25 g/L DPE, 1.5 g/L ZnO NPs, and 0.2 g/L SiO2 NPs treatments, and 32 in the 50% NPK, 25 g/L DPE, and 0.2 g/L SiO2 NPs treatments. Oxygenated hydrocarbons, sesquiterpenes, and monoterpenes varied by application. Thujone, camphor, manool, and ledol were the major constituents of the EO. Leaf chemical composition, antioxidant activity, and total phenolic compounds were significantly influenced by the treatments. In combination with DPE, ZnO and SiO2 NPs reduced the need for higher amounts of mineral NPK fertilizers. These agents can therefore be useful for advancing sustainable agricultural practices in novel and advantageous ways.